European Union Water Policy—Tasks for Implementing “WaterFrameworkDirective” in Pre-accession Countries - Sozen, S.; Avcioglu, E.; Ozabali, A.; Gorgun, E.; Orhon, D. (Informa UK Limited, 2003)
Water Framework Directive aiming to maintain and improve the aquatic environment in the EU was launched by the European Parliament in 2000. According to this directive, control of quantity is an ancillary element in securing good water quality and therefore measures on quantity, serving the objective of ensuring good quality should also be established. Accordingly, it is a comprehensive and coordinated package that will ensure all European waters to be protected according to a common standard. Therefore, it refers to all other Directives related to water resources management such as Urban Wastewater Treatment Directive Nitrates Directive, Drinking Water Directive, Integrated Pollution Prevention Control etc. Turkey, as a candidate state targeting full-membership, should comply the necessary preparations for the implementation of the "Water Framework Directive" as soon as possible. In this study, the necessary legislative, political, institutional, and technical attempts of the pre-accession countries have been discussed and effective recommendations have been offered for future activities in Turkey.
Keywords: International Cooperation; Water Pollution; Environment; Waste Disposal, Fluid; Europe; Water Supply; Humans; Policy Making